Efficacy of the Otago exercise programme as a supplementary intervention to exercise classes: On falls, balance, physical function and mobility in a patient with chronic lower back pain: A case report. - Rabilal, Melisha; Maharaj, Sonill S; Kaka, Bashir (Bangladesh Journal of Medical Science, 2020)
In the elderly, physical activity is essential in maintaining good health. In a resource constrained environment, where supervised exercise classes are conducted once a week, a suitable home exercise programme can provide the recommended weekly level of physical activity needed. The Otago Exercise Programme(OEP) is effective in the prevention of falls and increasing strength in the older adult. The efficacy of the OEP as a supplementary intervention to exercise classes; on falls, balance and health enhancing physical activity in the older adult with chronic lower back pain (CLBP) has not been reported. Mr X regularly attends the weekly land-based and aquatic exercise programme at a tertiary hospital in the public sector in Kwa Zulu-Natal. He demonstrated willingness to follow the OEP as prescribed by the Otago exercise manual as a home exercise programme and continued with other leisure, walking and activities of daily living. Post the exercise programme Mr X showed remarkable improvement in the chair to stand test, four-test balance scale and health enhanced physical activity. The OEP is effective and can be used as a supplemental programme to regular supervised exercise classes. The OEP can be beneficial for elderly patients with weakness and chronic lower back pain. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.339-342